Térközösségi, érdekközösségi, „sorsközösségi” államcsoportok formálódása az Európai Unió keleti térségében - Hajdú Zoltán („RIK-U” Kft., 2020)
A kétpólusú világ, a megosztott Európa összeomlása, a Szovjetunió és az európai szocialista föderációk (Csehszlovákia, Jugoszlávia) szétesése minden tekintetben új helyzetet teremtett egész Európában, de különösen Közép- és Kelet-Európában. Új államok születtek, új hatalmi, gazdasági, politikai törekvések jelentek meg. A különböző területi országcsoportok rövid bemutatásakor a „területi kör”, a „vállalt térközösség” bemutatására koncentrálunk amellett, hogy a funkcionális tartalom alakulására is kitérünk.

Abstract. The EU member states – partially due to external challenges and opportunities (China) and partially due to the increasingly evident internal interest fragmentation of the EU – parallelly consider their individual position, their grouping options and their ambitions to enforce interests. Hungary was the first to define its new position by publishing its “Carpathian Basin Concept”. The “Friends of Cohesion”, the Visegrad Four, the “New Central-Europe”, etc groups bear different emphases and open different action arenas. However, the new “homogenous territorial grouping” has not yet evolved, but this opportunity may also open up in the future.
Formation of common space, common interest and “common destiny” state groupings at the eastern territories of the European Union
https://kmf.uz.ua/wp-content/uploads/2020/09/final_1_kotet-foldrajzfkonf-2020-07-14.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008119
Keywords: Európai Unió; politikai együttműködés; az Európai Unió keleti térsége